2007
DOI: 10.1007/s10038-006-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 and its three gene polymorphisms relating to allergic rhinitis

Abstract: The study aimed to examine an association of three different single nucleotide polymorphisms (SNPs) of the IL-18 gene (-607 C/A, -137 G/C and -133 C/G) on chromosome 11q22 with allergic rhinitis (AR). Genotyping for the SNPs was performed using 539 patients with AR and 312 healthy control volunteers. Positivity to the skin prick test for the fungus Alternaria sp. in patients with AR, and IgE levels according to particular genotypes of selected SNPs, were also determined. There were no significant differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Given the multifactorial nature of allergic diseases and the critical role of IL-18 in the allergic response, the possible association of polymorphisms in the IL-18 gene with allergic states has been investigated. Previously we demonstrated association of three polymorphisms within the IL-18 gene with atopic phenotypes like elevated IgE levels and sensitization to Alternaria alternata in patients with allergic rhinitis [18]. In this study, we screened the same three SNPs together with a newly described putative functional polymorphism Ϫ1297 C/T alone and in combination (i.e., haplotypes) in Czech patients not only with allergic rhinitis but also with other frequent and important manifestations of allergic disorders, such as asthma and eczema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the multifactorial nature of allergic diseases and the critical role of IL-18 in the allergic response, the possible association of polymorphisms in the IL-18 gene with allergic states has been investigated. Previously we demonstrated association of three polymorphisms within the IL-18 gene with atopic phenotypes like elevated IgE levels and sensitization to Alternaria alternata in patients with allergic rhinitis [18]. In this study, we screened the same three SNPs together with a newly described putative functional polymorphism Ϫ1297 C/T alone and in combination (i.e., haplotypes) in Czech patients not only with allergic rhinitis but also with other frequent and important manifestations of allergic disorders, such as asthma and eczema.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Ϫ607 A/C (rs1946518), Ϫ137 C/G (rs187238) in the promoter region, and Ϫ140 C/G (previously Ϫ133 C/G, rs4988359) in intron 1 have been studied in detail with respect to etiopathogenesis of allergic diseases [15][16][17][18] and transcriptional activity or IL-18 production by monocytes [19 -21]. Current results have indicated the inconsistent association between IL-18 gene variants and clinical/ intermediary phenotypes of allergy in different populations [15][16][17][18][22][23][24][25][26][27][28][29][30][31]. However, a novel putative functional variant Ϫ1297 C/T (rs360719) within the IL-18 promoter region that seems to have an important role in IL-18 expression was recently associated with susceptibility to SLE [32].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have investigated single-nucleotide polymorphisms (SNPs) in genes encoding the molecules implicated in the pathogenesis of AR; including specific chemokines and their receptors [7,8], interleukins (ILs) and their receptors [9,10], eosinophil peroxidise [11] and leukotriene C4 synthase [12].…”
Section: Introductionmentioning
confidence: 99%
“…IL-18 has become recognized as an important regulator of innate and acquired immune responses and is expressed at sites of chronic inflammatory disease [10]. To date, accumulating evidence demonstrated that IL-18 synergizes with IL-12 to induce IFN- γ production and promote Th1 responses [11, 12].…”
Section: Introductionmentioning
confidence: 99%